The in vitro Effects of the Probiotic Strain, Lactobacillus casei ZX633 on Gut Microbiota Composition in Infants With Diarrhea - Wang, Xing; Zhang, Miao; Wang, Weidong; Lv, Haoxin; Zhang, Hua; Liu, Yuan; Tan, Zhongfang (Frontiers in Cellular and Infection Microbiology, 2020)
We investigated the in vitro effects of Lactobacillus casei ZX633 on gut microorganism composition in infants with diarrhea. For this purpose, 103 feces samples from healthy infants (healthy group) and 300 diarrhea samples from infants (diarrhea group) were collected, and diarrhea feces were treated with L. casei ZX633, which was previously isolated from healthy infant feces (treatment group). We used microbial dilution plate methods, high performance liquid chromatography (HPLC) and high-throughput sequencing approaches to analyze viable main microorganism counts, short chain fatty acid (SCFA) concentrations, and intestinal microbiota composition in feces, respectively. Our data showed that L. casei ZX633 supplementation increased the numbers of Escherichia coli, yeasts, lactic acid bacteria (LAB) and aerobic-bacteria, raised propionic acid levels but reduced four other SCFAs, which are close to the healthy group. Alpha diversity results indicated that microbial diversity and richness decreased in treatment group. Bacterial community analyses revealed that microbial structures of the treatment group tended towards the healthy group; i.e. Escherichia-Shigella and Clostridioides abundance increased, and there was a reduction in the abundance of Streptococcus, Bacteroides, Enterococcus and Veillonella. In conclusion, L. casei ZX633 isolated from healthy infant feces, may be effective in improving infant diarrhea microbiota, potentially providing a new probiotic strain to reduce the incidence of diarrhea associated with bacterial disease in infants.